1993
DOI: 10.1016/0927-7765(93)80042-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metallic ions on the adhesion of biofilms formed by Pseudomonas fluorescens

Abstract: Data on the adhesion of biofilms formed by Pseudomonas fiuorescens to aluminium, copper and brass surfaces are reported in this paper. Biofilm thicknesses after 48 h were lower on the brass plates than on the other two metals. The results are compared with predictions of bacterial adhesion obtained by the method of van O ss et al. (C.J. van Oss, M.K. Chaudhury and R.J. Good, Chern. Rev ., 88 (1988) 927), based on the evaluation of the change in the free energy of adhesion of the interacting systems. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Previous observations of biofilm-forming bacteria and aggregates on the macroscopic level have suggested polymer bridging as a mechanism for adhesion in biofilms. [34][35][36] The ability of polysaccharides to undergo the type of conformational changes necessary for bridging has recently been shown by other investigators using the AFM. 37 Polymer bridging behavior has been modeled by the Alexander and de Gennes modification 38 of the de Gennes scaling theory for polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations of biofilm-forming bacteria and aggregates on the macroscopic level have suggested polymer bridging as a mechanism for adhesion in biofilms. [34][35][36] The ability of polysaccharides to undergo the type of conformational changes necessary for bridging has recently been shown by other investigators using the AFM. 37 Polymer bridging behavior has been modeled by the Alexander and de Gennes modification 38 of the de Gennes scaling theory for polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of other cations is not predictable, mainly when microbial adhesion is concerned. A study on the adhesion of Pseudomonasfluorescens to copper, brass, and aluminum surfaces showed that the formation of deposits is delayed in the presence of Cu E+ and Zn 2+ ions because these ions have a pronounced inhibitory effect on the growth of this microorganism [28].…”
Section: + 2+mentioning
confidence: 99%
“…Both increased mass penetration to biofilm and greater bacterial density were observed within Pseudomoas fluorescens culture when incubated with increasing flow velocity (Vieira et al, 1993). Similarly, Lehtola et al (2006) observed that within pilot distribution system biofilm formation was favoured by increased flow velocity and accompanied with increasing consumption of nutrients.…”
Section: Hydraulic Impacts Upon Nitrificationmentioning
confidence: 85%
“…Hydraulic condition is considered to be an influencing factor due to its impact on mass transfer to biofilm, including nutrients, disinfectants, oxygen and microorganisms (Beer et al, 1996;Beyenal and Lewandowski, 2002;Vieira et al, 1993), and also on biofilm density, composition and structural characteristics (Abe et al, 2012;Purevdorj et al, 2002).…”
Section: Hydraulic Impacts Upon Nitrificationmentioning
confidence: 99%